Forns index predicts recurrence and death in patients with hepatitis B‐related hepatocellular carcinoma after curative resection. (22nd January 2015) - Choi, Won‐Mook; Lee, Jeong‐Hoon; Ahn, Hongkeun; Cho, Hyeki; Cho, Young Youn; Lee, Minjong; Yoo, Jeong‐ju; Cho, Yuri; Lee, Dong Hyeon; Lee, Yun Bin; Cho, Eun Ju; Yu, Su Jong; et al.
Abstract Background & Aims Advanced liver fibrosis is associated with recurrence after curative resection of hepatocellular carcinoma (HCC). This study aimed to investigate whether noninvasive fibrosis indices could predict intrahepatic recurrence and death after curative resection of HCC. Methods Patients who underwent curative resection for hepatitis B virus (HBV)‐related HCC between 2006 and 2010 at a single tertiary hospital were included. This study analysed the association of noninvasive fibrosis indices with recurrence and overall survival. Results A total of 303 patients were included. During a median follow‐up period of 56.0 (interquartile range, 42.0–70.0) months, 151 (49.8%) patients experienced HCC recurrence and 54 (17.8%) died. Based on multivariate analysis, Forns index [hazard ratio (HR), 1.238; 95% confidence interval (CI), 1.097–1.398; P = 0.001] was independently associated with tumour recurrence after adjustment for anti‐HBe positivity, histological cirrhosis, tumour size and number. Patients with Forns index <6.9 had a significantly longer recurrence‐free survival rate than patients with Forns index ≥6.9 (P < 0.001 by log‐rank test). Forns index (HR, 1.246; 95% CI, 1.034–1.501; P = 0.02) could also predict overall survival after adjustment for tumour size and number. Forns index detected cirrhosis with an AUROC of 0.700 (95% CI, 0.641–0.758). Aspartate aminotransferase‐to‐platelet ratio index, cirrhosis discriminant score, FIB‐4 index, P2/MS and Lok index detected cirrhosis comparably to Forns index, but were not associated with tumour recurrence or death. Conclusions Our data suggest that Forns index could be a useful predictor of recurrence and overall survival after curative resection of HBV‐related HCC.